2011
DOI: 10.1371/journal.pone.0022090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Cross-Interaction between APOE and PRNP in Sporadic Alzheimer's and Creutzfeldt-Jakob Diseases

Abstract: Alzheimer's disease (AD) and Creutzfeldt-Jakob disease (CJD) represent two distinct clinical entities belonging to a wider group, generically named as conformational disorders that share common pathophysiologic mechanisms. It is well-established that the APOE ε4 allele and homozygosity at polymorphic codon 129 in the PRNP gene are the major genetic risk factors for AD and human prion diseases, respectively. However, the roles of PRNP in AD, and APOE in CJD are controversial. In this work, we investigated for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
28
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 81 publications
(80 reference statements)
8
28
3
Order By: Relevance
“…In opposition to some studies, which showed interaction between ApoE and PRNP, our data did not reveal differences in codon 129 genotypes according to the ApoE status [13][14][15][16][17][18][19][20][21] . This study of PRNP in patients with AD in the Brazilian population has, as its main limitation, the small sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In opposition to some studies, which showed interaction between ApoE and PRNP, our data did not reveal differences in codon 129 genotypes according to the ApoE status [13][14][15][16][17][18][19][20][21] . This study of PRNP in patients with AD in the Brazilian population has, as its main limitation, the small sample.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies have shown that this polymorphism may be a risk factor for AD [12][13][14] . Others, however, failed to confirm such association 5,8,[15][16][17][18][19][20][21] . A meta-analysis concluded that codon 129 homozygosity of PRNP is a risk factor for AD in a Caucasian population 19 .…”
mentioning
confidence: 99%
“…Homozygosis at polymorphic codon 129 in the PRNP gene was shown to be strongly associated with sCJD (OR = 4.87, 95% CIs = 3.21-7.39, p = 8.49 × 10 -14 ) in agreement with a previous report for this population. 22 By sequencing analysis of the complete coding regions of the CALHM genes, we found eight single nucleotide polymorphisms (SNP) in CALHM1, 2 SNP in CALHM3, and none in CALHM2 ( Table 1). All of these SNPs were already identified in The Single Nucleotide Polymorphism Database (dbSNP) of Nucleotide Sequence Variation (www.ncbi.nlm.nih.gov/projects/SNP/index.html).…”
Section: Discussionmentioning
confidence: 99%
“…14 Several lines of evidence suggest that AD and prion diseases share pathophysiologic mechanisms. [15][16][17][18][19][20][21][22][23] In this paper, we investigated the genetic variability of the gene cluster formed by CALHM1 and its paralogs in a Caucasian population of Spanish origin, and explored the potential association of these genes with sporadic Creutzfeldt-Jakob disease (sCJD).…”
Section: Introductionmentioning
confidence: 99%
“…4 Codons 127 and 219 of PRNP also harbour amino-acid (AA) polymorphisms that confer resistance to Kuru 5 or sCJD. 6 Recently, other candidate genes have been identified as risk factors for sCJD, such as an SNP upstream of PRNP exon 1 (SNP 1368), 7 c.592C4T(p.T174M) in prion-like doppel gene (PRND), 8 APOE e4 allele, 9 polymorphisms at CALHM1 gene, 10 and BACE1 gene. 11 Identification of the potential genetic risk factors for sCJD seems to be one of the important pathways for understanding of the pathogenic mechanisms and human susceptibility to the disease.…”
Section: Introductionmentioning
confidence: 99%